THU0196 TOFACITINIB IN PATIENTS WITH RHEUMATOID ARTHRITIS AND INDICATIVE OF DEPRESSION AND/OR ANXIETY: A POST HOC ANALYSIS OF PHASE 3 AND PHASE 3B/4 CLINICAL TRIALS. (2nd June 2020) - Citera, G.; Jain, R.; Irazoque-Palazuelos, F.; Guzman, R.; Madariaga, H.; Gruben, D. C.; Wang, L.; Stockert, L.; Hsu, M. A.; Santana, K.; Ebrahim, A.; Ponce de Leon, D.
Abstract : Background: Depression/anxiety are common in RA pts. SF-36 MCS ≤38 can identify probable major depressive disorder and/or probable generalised anxiety disorder (pMDD/pGAD) in RA pts. Tofacitinib is an oral JAK inhibitor for the treatment of RA. Objectives: To assess pMDD/pGAD prevalence in the tofacitinib RA program and efficacy by baseline (BL) pMDD/pGAD status. Methods: Data from pts receiving tofacitinib, ADA, or PBO were pooled from 5 Phase (P)3 and 1 P3b/4 trials. Demographics/BL characteristics were reported by BL pMDD/pGAD (SF-36 MCS ≤38, presence; >38, absence). Month (M)3/6/9/12 SF-36 MCS change from BL (Δ) was estimated, and % with pMDD/pGAD reported. M3/6/12 efficacy outcomes compared tofacitinib-treated pts by BL pMDD/pGAD. Results: BL pMDD/pGAD was seen in 44.5% (tofacitinib 5 mg BID), 39.8% (tofacitinib 10 mg BID), 45.4% (ADA 40 mg Q2W) and 39.1% (PBO) of pts. pMDD/pGAD pts had higher BL CRP and worse disability, fatigue, pain and sleep vs pts without. SF-36 MCS increases were greater for tofacitinib vs PBO/ADA (Fig 1a). The % of pts with BL pMDD/pGAD who continued to have pMDD/pGAD reduced over time, and was generally lower for tofacitinib vs PBO/ADA (Fig 1b). Regardless of BL pMDD/pGAD, efficacy was generally similar for tofacitinib 5 mg BID (Table) and 10 mg BID. Conclusion: 40% of RA pts had BL pMDD/pGAD. SF-36 MCS improvements were greater for tofacitinib vs PBO/ADA. With tofacitinib, % of pts with SF-36 MCS ≤38 reduced by 60% at M12. Tofacitinib efficacy was similar in pts with/without BL pMDD/pGAD. Limitations include using SF-36 MCS to identify probable rather than confirmed MDD or GAD. Future research using gold standard psychiatric interviews to validate use of SF-36 MCS ≤38 is needed. Acknowledgments: Study sponsored by Pfizer Inc. Medical writing support was provided by Sarah Piggott of CMC Connect and funded by Pfizer Inc. Disclosure of Interests: Gustavo Citera Grant/research support from: AbbVie, Amgen, Eli Lilly, Gema, Genzyme, Novartis and Pfizer Inc, Consultant of: AbbVie, Amgen, Eli Lilly, Gema, Genzyme, Novartis and Pfizer Inc, Rakesh Jain Grant/research support from: Allergan, Eli Lilly, Lundbeck, Otsuka, Pfizer Inc, Shire and Takeda, Consultant of: Acadia, Alfasigma, Allergan, Eisai, Eli Lilly, Evidera, Impel, Janssen, Lundbeck, Merck, Neos Therapeutics, Neurocrine Biosciences, Osmotica, Otsuka, Pamlab, Pfizer Inc, Shire, Sunovion, Supernus, Takeda and Teva, Speakers bureau: Alkermes, Allergan, Eli Lilly, Janssen, Lundbeck, Merck, Neos Therapeutics, Neurocrine, Otsuka, Pamlab, Pfizer Inc, Shire, Sunovion, Takeda, Teva and Tris Pharmaceuticals, Fedra Irazoque-Palazuelos Consultant of: Bristol-Myers Squibb, Janssen, Pfizer Inc, Roche and UCB, Renato Guzman: None declared, Hugo Madariaga: None declared, David C Gruben Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Lisy Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Lori Stockert Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Ming-Ann Hsu Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Karina Santana Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Abbas Ebrahim Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Dario Ponce de Leon Shareholder of: Pfizer Inc, Employee of: Pfizer Inc